High concentration of extracellular nucleotides suppresses cell growth via delayed cell cycle progression in cancer and noncancer cell lines. Issue 11 (November 2021) - Sawa, Chika; Yofu, Sachiko; Kiriyama, Keisuke; Sutoh, Keita; Saito, Tomomi; Kishi, Satomi; Gunji, Mariko; Inoue, Yuriko; Sugi, Masahito; Shioda, Seiji; Honda, Kazuho
Abstract: Tumor necrosis frequently occurs in malignant tumors, showing rapid growth and invasion. This phenomenon is generally regarded as simple ischemic necrosis due to insufficient tumor vessels and blood supply. However, the necrotic tissue contains high amount of nuclear substances, DNA, and nucleoproteins that may affect the surrounding tumor cells by promoting or suppressing the tumor cell growth in vivo . This study focused on the effects of an externally administered water-soluble nuclear crude extract (SNE) containing nuclear protein and oligonucleotides on several human cancer and noncancer cell lines. The results demonstrated that the SNE suppressed cell growth in cancer and noncancer cells in vitro . Through the flow cytometry analysis of the nuclear DNA content, it was observed that the SNE increased and decreased cell proportion in the S and G2/M phases, respectively, thereby suggesting that the cell growth inhibition was due to cell cycle delay, and not due to apoptosis. These studies suggest that the high-concentration of extracellular nucleotides generated as a result of tumor necrosis and/or released from infiltrated neutrophils could suppress the growth of surrounding cancer and intrinsic cells, which provides us some insights into an alternative anticancer strategy for patients with highly malignant necrotic tumor. Abstract : Tumor necrosis; Extracellular nucleotide; Cell proliferation; Cell cycle delay; Neutrophil extracellular traps.